2022
DOI: 10.1142/s0219455422501735
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Characteristic Analysis of Tunnel Structure Buried in Elastic Foundation Based on Dynamic Stiffness Matrix

Abstract: In this study, the free vibration characteristics of a non-circular tunnel buried in a Winkler foundation are first investigated based on a dynamic stiffness approach and the Wittrick–Williams algorithm. The non-circular tunnel was modeled as a shell composed of multipartial circular cylinders based on the first shear deformation Flügge shell theory, by which the effects of shear deformation and moment of inertia were considered. The transfer function of the state variable was derived, and the elementary dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…According to engineering practice, it is found that the dynamic characteristics of the mechanical structure of the device are often concentrated in low-order modes, and the low frequency vibration wavelengths are longer. The vibration analysis under the low-order modal of the device is the key to the research of intensity failure and stability [5]- [8]. In order to simulate the power characteristics of as much as possible at high and low frequency, the first six-order modes are analyzed and calculated.…”
Section: Modal Analysis Calculationmentioning
confidence: 99%
“…According to engineering practice, it is found that the dynamic characteristics of the mechanical structure of the device are often concentrated in low-order modes, and the low frequency vibration wavelengths are longer. The vibration analysis under the low-order modal of the device is the key to the research of intensity failure and stability [5]- [8]. In order to simulate the power characteristics of as much as possible at high and low frequency, the first six-order modes are analyzed and calculated.…”
Section: Modal Analysis Calculationmentioning
confidence: 99%